Persepsi Customer Experience, Service Quality, dan Product Quality terhadap Kepuasan Pelanggan di Warung Kopi Sinar Gemilang Kota Tegal - Muhammad Syadan Farizi; Syah Rafi Kafabih; Risma Indah Farrawansyah; Sari Wiyanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of customer experience perception, service quality, and product quality on customer satisfaction at Sinar Gemilang Coffee Shop. Using a quantitative approach, data were collected through a structured questionnaire survey of customers. The findings indicate that customer experience perception, service quality, and product quality have a positive and significant impact on customer satisfaction, both partially and simultaneously. Customer experience perception plays a major role in fostering loyalty through meaningful and consistent interactions. Meanwhile, service quality is crucial in building customer trust through friendliness, responsiveness, and reliability. Product quality is also a key factor, as aspects such as taste, consistency, and value directly enhance customer satisfaction. These findings offer practical implications for Sinar Gemilang Coffee Shop to continually improve customer experience, service, and product quality to maintain competitiveness and increase customer satisfaction.